VD_FINDINFO HC / 2010 / 302 vom 29. März 2010 - VD Tribunal cantonal (2010)
BAIL À LOYER, AUGMENTATIONEN GÉNÉRAL, MÉTHODE RELATIVE, PLUS-VALUE, AMORTISSEMENT{ÉCONOMIE} | 269a let. b CO, 451 ch. 2 CPC, 452 al. 1 CPC, 452 al. 2 CPC, 14 OBLF